Prinsip Perkawinan Islam Ditinjau Dari Perspektif Psikologi - Vira Primanugrah Shakanti; Dini Rahma Bintari (Jurnal Kajian Ilmiah, 2023)
The commands and prohibitions in the Islamic principles in marriage that are applied to humans are created upon human characteristics and nature. Every individual has psychological uniqueness, so in order to understand family life, it is required to take a psychological approach. To improve the quality of marriage, it is necessary to conduct a study about the Islamic principles on marriage and the views from psychological perspective in its implementations. This study aims to explain the principles of marriage in Islam and the psychological symptoms that come along with them. The study method is literature study with descriptive analysis technique. The Islamic principles on marriage that are discussed in this article are divided into principles in premarital life, married life, and divorce. Psychological symptoms that arise in the implementation of the Islamic principles in marriage proved that the instructions regarding marriage life in the Alquran and hadith have a good impact on one’s mental condition, and prohibitions exist to help avoid any mental discomforts.